2016
DOI: 10.1111/acer.13110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varenicline Combined with High-Dose Alcohol on Craving, Subjective Intoxication, Perceptual Motor Response, and Executive Cognitive Function in Adults with Alcohol Use Disorders: Preliminary Findings

Abstract: Background Varenicline has been found to decrease alcohol-motivated behaviors. Recent warnings regarding aversive events associated with varenicline used in conjunction with alcohol warrant further investigation into the safety of the drug when combined with alcohol. The purpose of this preliminary investigation was to examine the effect of combining varenicline with a high, fixed-dose of alcohol on subjective reactivity and cognitive function in adults with alcohol use disorders. Methods This double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Early reports of VAR‐induced altered behavior, which resulted in a 2015 FDA warning regarding the use of VAR, were not substantiated and the FDA revised the warning in 2016 and stated that VAR does not pose serious mental health risks. Importantly, there appears to be minimal side effects of VAR reported in individuals with AUD (McKee et al., ; Mitchell et al., ; Verplaetse et al., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Early reports of VAR‐induced altered behavior, which resulted in a 2015 FDA warning regarding the use of VAR, were not substantiated and the FDA revised the warning in 2016 and stated that VAR does not pose serious mental health risks. Importantly, there appears to be minimal side effects of VAR reported in individuals with AUD (McKee et al., ; Mitchell et al., ; Verplaetse et al., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…The beta‐endorphin response to alcohol is heritable (Froehlich et al., ) and the response is greater in individuals with a family history of alcoholism than it is in individuals without a family history of alcoholism (Gianoulakis et al., ). Both NTX and VAR reduce alcohol‐induced feelings of intoxication and well‐being and reduce alcohol drinking (Chick et al., ; Childs et al., ; Froehlich et al., ; Hendershot et al., ; Litten et al., ; McKee et al., ; O'Malley and Froehlich, ; Verplaetse et al., ; Volpicelli et al., ). NTX is more effective in decreasing alcohol drinking in individuals with a family history of alcoholism (“family history positive” or “high risk”) than in individuals without a family history of alcoholism (Krishnan‐Sarin et al., ; Monterosso et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…All participants were heavy drinkers who reported consuming > 7 (women) or 14 (men) drinks per week and > 3 (women) or > 4 (men) drinks per episode in the last 30 days. Participants were recruited as part of larger series of sequential human laboratory studies, the results of which are reported elsewhere (McKee et al 2009; Verplaetse et al 2016a; Verplaetse et al 2016b). Data reported in McKee et al (2009) and Verplaetse et al (2016a) were collected 8 post-randomization and reported on ad-libitum drinking outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Data reported in McKee et al (2009) and Verplaetse et al (2016a) were collected 8 post-randomization and reported on ad-libitum drinking outcomes. Data reported in Verplaetse et al (2016b) were collected between 2 and 3 weeks post-randomization and reported on reactivity to a high dose of alcohol. Data reported in the current manuscript has not been previously published and were collected on a separate laboratory session (day 10 post-randomization).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation